ANALISIS RENCANA DAN PELAPORAN PERTANGGUNGJAWABAN PENGELOLAAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) TERHADAP TRANSPARANSI KEUANGAN TAHUN 2019: (STUDI KASUS PADA SDN CAKUNG BARAT 04 PAGI) - Idward Resha Indiarto; Adam, Adam; Rina Pratiwi, Rina Pratiwi (Cakrawala Akuntansi & Manajemen, 2024)
School Operational Assistance (BOS) is a Government program to provide non-personnel fee funding for basic education units as implementers of compulsory education programs. Bos fund aims to ease the burden on the community on education financing in the framework of quality 12-year compulsory education. BOS funds are distributed based on student data (Dapodik) in the school every year. In the management of BOS Funds, accountability and transparency are needed for the use of BOS funds. Transparency is an openness in the delivery of data or information. In terms of the delivery of information data to the public. The School is faced with valid BOS fund management, containing RKAS Plan, Actualization / Realization of bos funds use, the contents of reports that include SPJ, receipts, accountability for reports and actions and policies made in terms of BOS fund management. In this case, SDN Cakung Barat 04 Am in terms of bos fund management using the cash base accrual method, as well as using the zero basic method, where each fund received must be maximized effectively and efficiently, because the zero basic method emphasizes on the amount of cash out must be zero at the end of the period. If there are still remaining BOS funds that are not absorbed, then the funds are returned to the Government. Based on the results of budget absorption research and realization of 99.16%, Design distribution, plan, transparency fund management has been implemented effectively and efficiently, Planning that has been running with deliberation involving all parties, Tiered reporting is already underway, the unavailability of special human resources to manage BOS funds, there are still school residents who still do not understand the transparency of BOS fund management.